The Ecological Taxation as an Instrument of Influence on the Volumes of Waste Generation: Implementing the European Experience in Ukraine - Honcharuk Inna V.; Yemchyk Tetiana V.; Vovk Valeriia Yu. (Bìznes Inform, 2022)
The purpose of the article is to study the systems of ecological tax collection in Ukraine and Europe, as well as to substantiate proposals for improving the mechanism for calculating, distributing and using ecological tax funds in Ukraine, using the EU experience. The authors characterize the system of ecological taxation in the EU member states and make a comparison of the types of ecological taxes levied in the EU-27 countries and in Ukraine. An analysis of the volumes of waste generation, CO2 emissions and ecological tax revenues in the EU-27 countries was carried out. It is observed that there is a directly proportional relationship between the volumes of waste generation, CO2 emissions and the amount of revenues from the payment of ecological taxes in the EU-27 countries, that is, with an increase (decrease) in the value of one of them several times, the value of another value increases (decreases) by the same number of times. The revenues from ecological taxes in incomes and the share of ecological taxes in the overall structure of tax revenues of some European countries and Ukraine were analyzed. The model of the impact of ecological tax regulation on decision-making by ecological polluters is presented, the main problems that currently exist in the domestic system of ecological tax collection are identified and measures to solve these problems are proposed. Simultaneously, it is determined that the proposed measures to increase ecological tax rates can lead to serious risks in the implementation of production and economic activities by enterprises. In view of the above-mentioned, the need for further research is to improve the system of targeted allocation of funds from the payment of ecological taxes and financing of ecological measures and the introduction of energy- and resource-saving low-waste and waste-free technologies at enterprises